DNase1: No Association with Crohn's Disease in a New Zealand Population. (4th June 2012) - Morgan, Angharad R.; Lam, Wen-Jiun; Han, Dug-Yeo; Fraser, Alan G.; Ferguson, Lynnette R.
Abstract : DNase1 has been implicated in a number of immune disorders and is an excellent candidate gene for Crohn's disease (CD). We investigated whether DNase1 SNPs rs1053874 and rs8176938 were associated with CD in a well-characterized New Zealand dataset consisting of 447 cases and 716 controls. Furthermore, we measured serum DNase1 activity levels in a number of CD patients and controls. We did not find any evidence of association for either DNase1 genetic variation or DNase1 activity levels with CD. The lack of association indicates that DNase1 does not play a significant role in predisposing to CD in the New Zealand population.